Kaluza-Klein five-point functions from AdS5×S5 supergravity - Vasco Gonçalves; Carlo Meneghelli; Raul Pereira; Joao Vilas Boas; Xinan Zhou (Journal of High Energy Physics, 2023)
Abstract We continue to explore the bootstrap approach to five-point correlation functions for IIB supergravity on AdS 5 × S 5. Building on the result of [1], we develop an improved algorithm that allows us to more efficiently compute correlators of higher Kaluza-Klein modes. The new method uses only factorization and a superconformal twist, and is entirely within Mellin space where the analytic structure of holographic correlators is simpler. Using this method, we obtain in a closed form all five-point functions of the form 〈pp222〉, extending the earlier result for p = 2. As a byproduct of our analysis, we also obtain explicit results for spinning four-point functions of higher Kaluza-Klein modes.